Management of connective tissue diseases in primary care [Birinci basamakta baǧ dokusu hastaliklarina yaklaşim] - (:unkn) unknown (My University, 2007)
The most common autoimmune rheumatologic diseases which could be frequently seen in primary care; Rheumatoid Arthritis (RA) (1-3 %), Systemic Lupus Erythematosis (SLE) (0.54 %) and Behçet's Disease (BD) (0.08-0.37 %) differ from each other regarding treatment and follow-up, so should be differentiated. To diagnose these diseases at primary care setting can be problematic, because the rheumatological symptoms and signs vary widely and the specific auto-antibodies of the suggested diseases could only be done at secondary or tertiary fascilities. On the other hand, similar diagnosing processes and appropriate algorithms could help primary care physician during differential diagnosis and appropriate consultation of rheumatological patient. The following review is prepared for primary care physicians to gather necessary information for outpatient practice about the diagnostic criteria, clinical features, emergency situations, choice and interpetation of simple laboratory tests of autoimmune rheumatolocal diseases (connective tissue diseases) in which we experience difficulty in diagnosing and choosing treatment options time to time.